Proposition for treatment of solid residues in the district of Santa Rosa de Quives, prov. de Canta depto. de Lima - Gallarday Bocanegra, Tomás (2009)
The management and treatment given to solid waste or residues in the Santa Rosa de Quives district is not the same as that given to other public services. The current management has no interest in technically eliminating domestic solid waste (RSD), they are considered insignificant, generated on a small scale by the district neighborhood. The treatment in its stages of collection, loading, transport, deposit and disposal is developed in part by the population, according to their cultural level or knowledge they have on the subject, it is what generates it in the annexes, towns and units agricultural. The RS are collected at home in Apan, Buena Vista, Cocayalta, Leticia, Magdalena, Huarhuar, Pampacocha, Pichupichu; In the other towns such as Macas, Olivar, Sapán, Santa Rosa de Quives, Trapiche, Yangas and Yaso, the municipality does the cleaning, with sorting, storage, loading, transport, storage and disposal. Initially, the RS are deposited in cylinders and collectors with the municipal logo. They are located in the parks. One of these containers is a collector for batteries, batteries and glass; From all of them, the RSD are extracted, loaded, transported and eliminated in an irregular way, for this reason, the personnel who do it are exposed to contamination hazards. The generation of SR in these villages has been evaluated, the result has been used to develop technical standards, which were made known to the population. Emphasis was placed on the phrase "all families generate garbage, therefore, they pollute the environment, which is why they must contribute to cleaning it."